Impacts of Water Pollution on Nairobi River, Kenya: A Critical Literature Review - W, Rosetta (Journal of Physical Sciences, 2022)
Purpose: This study aimed at evaluating the impact of water pollution and bacteria on physio-chemical parameters, macroinvertebrates and algae in Nairobi River. Methodology: The paper used a desk study review methodology where relevant empirical literature was reviewed to identify main themes and to extract knowledge gaps. Conclusion: Pollution increases in the river as one moves down from Ondiri Swamp to Ruai and comprises mainly of solid wastes, raw sewage and industrial wastes. There is adequate evidence of fecal pollution in Nairobi River with levels far exceeding limits set by KBS (1996). This means that the river water is a health hazard and is not fit for human and animal consumption as well as for other domestic and industrial uses. Recommendations: Sustainable use and conservation of freshwater resources, water pollution control and prevention and institutional capacity building. Continuous monitoring and assessment of different pollution trends occurring within the river system should be carried out.